Coming to America: Does Having a Developed Home Country Matter for Self-Employment in the United States? - Oyelere, Ruth Uwaifo; Belton, Willie (American Economic Review, 2012)
This research examines the relationship between the economic status of an immigrant's home country and the probability of self-employment in the US. We find that immigrants from developing countries on average have lower self-employment probabilities relative to immigrants from developed countries. Similarly, we find a positive correlation between the current HDI of an immigrant's home country and the probability of self-employment in the US. These result are unexpected given that past research suggests immigrants from countries with high levels of self-employment (developing countries) are more likely to be self-employed in the US. We provide a possible explanation for these results.